Application of spin markers for study of liposome prepared by the modified reverse-phase evaporation method. Issue 1 (2008) - Pentak Pentak, Danuta Danuta; Sułkowski Sułkowski, Wiesław W. Wiesław W.; Wolińska Wolińska, Agnieszka Agnieszka; Maślanka Maślanka, Sławomir Sławomir; Bojko Bojko, Barbara Barbara; Maciążek Maciążek, Małgorzata Małgorzata; Równicka Równicka, Joanna Joanna; Sułkowska Sułkowska, Anna Anna
Abstract : The EPR spectroscopy was used to determine the structure and physicochemical properties of liposomes prepared from L-α-phosphatidylcholine dipalmitoyl (DPPC) by the modified reverse-phase evaporation method (mREV). EPR study was carried out in the temperature range from 297 K to 340 K i.e. below and above the phase transition temperature T C of DPPC. On the basis of EPR spectra of spin marker 2, 2, 6, 6-tetramethyl-1-piperidinyloxy (TEMPO) incorporated into the liposome, the parameter f was determined. TEMPO dissolves easily in water and in the fluid lamellar smectic liquid-crystaline phase of lipid bilayer but is largely excluded from the solid, gel-phase. Thus TEMPO can be used to observe the change in the partition between aqueous and fluid lipid regions. The change in the relative value of f as a function of temperature for DPPC shows that, in the presence of water excess, this phospholipids undergoes a transition from a "gel phase" to a lamellar smectic liquid crystalline phase. On the basis of EPR spectra of spin marker 2-(3carboxypropyl)-4, 4-dimethyl-2-tridecyl-3-oxazolidinloxyl (5-DOXYL) incorporated into liposome, the parameter a 'N was determined. The isotropic 14 N-hyperfine coupling constant a 'N of nitroxide spin label depends on the local environmental polarity. The increase of a 'N value reflects the rise of polarity of spin label environment. Temperature, cholesterol and pH dependent structural changes were also described.